2007
DOI: 10.1590/s1413-70542007000200035
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de níveis de lisina digestível verdadeira e proteína bruta na dieta sobre parâmetros morfo-fisiológicos e utilização do nitrogênio em suínos na fase inicial

Abstract: RESUMOFoi conduzido um experimento no Departamento de Zootecnia da Universidade Federal de Lavras para verificar a influência de diferentes níveis de proteína bruta (PB) e lisina digestível verdadeira (LISD) na dieta sobre peso de órgãos, parâmetros fisiológicos e utilização do nitrogênio (N) de rações por leitões na fase inicial. Foram utilizados 80 suínos machos castrados e fêmeas (peso inicial = 9,1 ± 1,2 kg e final = 21,5 ± 4,8 kg), mestiços (Landrace x Large White), desmamados aos 28 dias, alojados em gru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
(9 reference statements)
1
4
0
Order By: Relevance
“…According to these results, the increase in energy level decreases the efficiency of absorption of amino acids, especially when they are unbalanced in the diet. This reinforces the proposal by Zangeronimo et al (2007) that the energy levels of the diets could interfere in the utilization of dietary nitrogen, especially in diets with low levels of CP, where the smallest increase caloric provided by these diets could lead to a greater amount of net energy available to animals and interference in the processes of deamination and transamination of amino acids. This, somehow, can also be true in the epithelial tissue of the mucosa of the gastrointestinal tract, i.e., excess dietary energy may have reduced the use of amino acids for this purpose.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…According to these results, the increase in energy level decreases the efficiency of absorption of amino acids, especially when they are unbalanced in the diet. This reinforces the proposal by Zangeronimo et al (2007) that the energy levels of the diets could interfere in the utilization of dietary nitrogen, especially in diets with low levels of CP, where the smallest increase caloric provided by these diets could lead to a greater amount of net energy available to animals and interference in the processes of deamination and transamination of amino acids. This, somehow, can also be true in the epithelial tissue of the mucosa of the gastrointestinal tract, i.e., excess dietary energy may have reduced the use of amino acids for this purpose.…”
Section: Resultssupporting
confidence: 85%
“…Zangeronimo et al (2007) also found no differences in the percentages of AN by reducing the dietary crude protein percentage in four units for growing animals.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Some works have showed that the nutrient manipulations in diet can influence the performance (AROUCA et al, 2007;ZANGERONIMO et al, 2009), nitrogen metabolism ZANGERONIMO et al, 2007a), physiologic parameters (ZANGERONIMO et al, 2007b) and carcass composition (OLIVEIRA et al, 2006). Other ones (SUSENBETH, 1995;TRINDADE NETO et al, 2004) observed differences in the protein deposition tax in detriment of lipid in pigs in nursery phase manipulating only the lysine levels in the diet.…”
Section: Introductionmentioning
confidence: 99%
“…Some works have shown that nutrient manipulations in diets can influence the performance (AROUCA et al, 2007;ZANGERONIMO et al, 2009), nitrogen metabolism (OLIVEIRA et al, 2005;ZANGERONIMO et al, 2007a), physiologic parameters (ZANGERONIMO et al, 2007b) and carcass composition of swine .…”
mentioning
confidence: 99%